2018
DOI: 10.1111/pedi.12761
|View full text |Cite
|
Sign up to set email alerts
|

Treatment adherence and BMI reduction are key predictors of HbA1c 1 year after diagnosis of childhood type 2 diabetes in the United Kingdom

Abstract: Adherence to treatment and a reduction in BMI appear key to better outcomes a year after T2DM diagnosis. Retention and clinic attendance are concerning. The prevalence of microalbuminuria has increased 4-fold in the year following diagnosis and was associated with higher HbA1c.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
1
10
1
Order By: Relevance
“…Though there are likely many contributions to this disparity, including both psychosocial and physiologic factors, medication adherence is a key determinant of treatment responsiveness in the pediatric population, as higher HbA1c and poorer glycemic control has been linked with reduced metformin adherence in adolescence 6 . Specifically, suboptimal metformin adherence in youth may be the result of two key factors: metformin is associated with high rates of gastrointestinal (GI) side effects, and when using the standard release (SR) formulation, the twice daily dosing may be associated with significant medication burden 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Though there are likely many contributions to this disparity, including both psychosocial and physiologic factors, medication adherence is a key determinant of treatment responsiveness in the pediatric population, as higher HbA1c and poorer glycemic control has been linked with reduced metformin adherence in adolescence 6 . Specifically, suboptimal metformin adherence in youth may be the result of two key factors: metformin is associated with high rates of gastrointestinal (GI) side effects, and when using the standard release (SR) formulation, the twice daily dosing may be associated with significant medication burden 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Adherence is a crucial parameter of treatment success, considering there is evidence for a direct association between high adherence and better clinical outcomes (Candler et al, 2018;Matsuzawa et al, 2019). Adherence is a crucial parameter of treatment success, considering there is evidence for a direct association between high adherence and better clinical outcomes (Candler et al, 2018;Matsuzawa et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we will evaluate adherence to self‐control training as a marker of treatment feasibility, prior to evaluating its effects in a randomized controlled trial or an RCT (Naets et al, ). Adherence is a crucial parameter of treatment success, considering there is evidence for a direct association between high adherence and better clinical outcomes (Candler et al, ; Matsuzawa et al, ). It is recognized as a general threat in several nonpharmacological chronic disease interventions (Cheiloudaki & Alexopoulos, ; Dunbar‐Jacob & Mortimer‐Stephens, ).…”
Section: Introductionmentioning
confidence: 99%
“…6 More recently, Candler et al reported on the outcome from the British pediatric Surveillance Unit and identified weight loss as a predictor of improved glycemic control, which was not previously reported in the TODAY study. 17 It remains unclear if certain risk factors contributing to glycemic control are cohortspecific.…”
mentioning
confidence: 99%